Prevention of EloR/KhpA heterodimerization by introduction of site-specific amino acid substitutions renders the essential elongasome protein PBP2b redundant in Streptococcus pneumoniae - Winther, Anja Ruud (Sci Rep, 2019)
The RNA binding proteins EloR and KhpA are important components of the regulatory network that controls and coordinates cell elongation and division in S. pneumoniae. Loss of either protein reduces cell length, and makes the essential elongasome proteins PBP2b and RodA dispensable. It has been shown previously in formaldehyde crosslinking experiments that EloR co-precipitates with KhpA, indicating that they form a complex in vivo. In the present study, we used 3D modeling and site directed mutagenesis in combination with protein crosslinking to further study the relationship between EloR and KhpA. Protein-protein interaction studies demonstrated that KhpA forms homodimers and that KhpA in addition binds to the KH-II domain of EloR. Site directed mutagenesis identified isoleucine 61 (I61) as crucial for KhpA homodimerization. When substituting I61 with phenylalanine, KhpA lost the ability to homodimerize, while it still interacted clearly with EloR. In contrast, both homo- and heterodimerization were lost when I61 was substituted with tyrosine. By expressing these KhpA versions in S. pneumoniae, we were able to show that disruption of EloR/KhpA heterodimerization makes the elongasome redundant in S. pneumoniae. Of note, loss of KhpA homodimerization did not give rise to this phenotype, demonstrating that the EloR/KhpA complex is crucial for regulating the activity of the elongasome. In support of this conclusion, we found that localization of KhpA to the pneumococcal mid-cell region depends on its interaction with EloR. Furthermore, we found that the EloR/KhpA complex co-localizes with FtsZ throughout the cell cycle.